2006
DOI: 10.1021/ac0600407
|View full text |Cite
|
Sign up to set email alerts
|

Mass Defect Labeling of Cysteine for Improving Peptide Assignment in Shotgun Proteomic Analyses

Abstract: A method for improving the identification of peptides in a shotgun proteome analysis using accurate mass measurement has been developed. The improvement is based upon the derivatization of cysteine residues with a novel reagent, 2,4-dibromo-(2'-iodo)acetanilide. The derivitization changes the mass defect of cysteine-containing proteolytic peptides in a manner that increases their identification specificity. Peptide masses were measured using matrix-assisted laser desorption/ionization Fourier transform ion cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 29 publications
0
55
0
1
Order By: Relevance
“…Hernandez et al reported the derivatization with 2,4-dibromo-(2 0 -iodo)acetanilide. The derivatization rendered cysteinyl peptides more hydrophobic and was evaluated to enhance their detection (Hernandez et al, 2006). Indeed, MALDI Fourier transform ion cyclotron resonance (FTICR) MS of bovine serum albumin (BSA) tryptic digests modified with the reagent detected an average of 15.5 cysteine residues, whereas an average of 5 and 11.3 was found in the mass spectra of the control digests; respectively, not alkylated and alkylated with iodoacetamide.…”
Section: B Ionization Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Hernandez et al reported the derivatization with 2,4-dibromo-(2 0 -iodo)acetanilide. The derivatization rendered cysteinyl peptides more hydrophobic and was evaluated to enhance their detection (Hernandez et al, 2006). Indeed, MALDI Fourier transform ion cyclotron resonance (FTICR) MS of bovine serum albumin (BSA) tryptic digests modified with the reagent detected an average of 15.5 cysteine residues, whereas an average of 5 and 11.3 was found in the mass spectra of the control digests; respectively, not alkylated and alkylated with iodoacetamide.…”
Section: B Ionization Efficiencymentioning
confidence: 99%
“…When associated with accurate peptide mass measurements for rapid and unambiguous identification of proteins (AMT methodology), it clearly provides a gain (Goodlett et al, 2000). Without MS/MS measurements, mass-defect labels (MDL) for cysteines allowed to artificially differentiate cysteine-containing peptides from others with FTICR MS (Hernandez et al, 2006). Determination, and especially counting of, peptidic cysteines with tags [by simple post-column treatment for instance (Dayon et al, 2005b)] seem valuable in such a context.…”
Section: A About Cysteine Raritymentioning
confidence: 99%
“…Without any modifications, the most common naturally occurring 20 amino acids in proteins contain the elements C, H, N, O and S. On such a scale, the mass defects of other elements commonly found in amino acids differ negligibly from that of carbon: 14 N is 0.0031 amu, 16 O is −0.0051 amu, and 1 H is 0.0078 amu. The mass defect for 31 S, a much less frequently encountered element in protein, is rather larger, being −0.0279. Similarly, 31 P has a negative mass defect (−0.0262) that is significantly larger than most other commonly found atoms in biomolecules.…”
Section: Introductionmentioning
confidence: 98%
“…The mass defect for 31 S, a much less frequently encountered element in protein, is rather larger, being −0.0279. Similarly, 31 P has a negative mass defect (−0.0262) that is significantly larger than most other commonly found atoms in biomolecules. When it is present on proteins in the form of a phosphate group (net addition of HPO 3 ), the total mass deficit shifts by −0.0337.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the importance of cysteine-rich sequences for defining the border for unoccupied mass spectral space is limited due to the possibility of long aliphatic chain attachment as well as to the low abundance of cysteine in naturally-occurring proteins. The mass defect labeling of Cys on peptides has been shown to be a valuable approach for improving proteome analysis [10].…”
Section: Theoretical Changes In the Averagine-scale Mass Defect Upon mentioning
confidence: 99%